A Closer Look at Socioemotional Wealth: Its Flows, Stocks, and Prospects for Moving Forward. (March 2015) - Chua, Jess H.; Chrisman, James J.; De Massis, Alfredo
We supplement the recent work by Miller and Le Breton–Miller by evaluating more closely two related theoretical aspects of the socioemotional wealth concept: (1) the stocks and flows of noneconomic benefits and how they influence family firm behavior; and (2) the use of prospect theory as an umbrella concept. We, thus, contribute to family business research by delineating a number of important research questions related to these two theoretical aspects that need to be addressed if theories of family firm behavior and performance are to move forward.